Effect of Chronic Exposure to Textile Wastewater Treatment Plant Effluents on Growth Performance, Oxidative Stress, and Intestinal Microbiota in Adult Zebrafish (Danio rerio) - Wang, Chun; Yuan, Zixi; Sun, Yingxue; Yao, Xiaolong; Li, Ruixuan; Li, Shuangshuang (Frontiers in Microbiology, 2021)
The ever-increasing production and processing of textiles will lead to greater risks of releasing pollutants into the environment. Textile wastewater treatment plants (TWTPs) effluent are an important source of persistent toxic pollutants in receiving water bodies. The effects of specific pollutants on organisms are usually studied under laboratory conditions, and therefore, comprehensive results are not obtained regarding the chronic combined effects of pollutants under aquatic environmental conditions. Thus, this study aimed to determine the combined effects of TWTP effluents on the growth performance, oxidative stress, inflammatory response, and intestinal microbiota of adult zebrafish (Danio rerio). Exposure to TWTP effluents significantly inhibited growth, exacerbated the condition factor, and increased the mortality of adult zebrafish. Moreover, markedly decreases were observed in the activities of antioxidant enzymes, such as CAT, GSH, GSH-Px, MDA, SOD, and T-AOC, mostly in the intestine and muscle tissues of zebrafish after 1 and 4 months of exposure. In addition, the results demonstrated that TWTP effluent exposure affected the intestinal microbial community composition and decreased community diversity. Slight changes were found in the relative abundance of probiotic Lactobacillus, Akkermansia, and Lactococcus in zebrafish guts after chronic TWTP effluent exposure. The chronic toxic effects of slight increases in opportunistic pathogens, such as Mycoplasma, Stenotrophomonas, and Vibrio, deserve further attention. Our results reveal that TWTP effluent exposure poses potential health risks to aquatic organisms through growth inhibition, oxidative stress impairment of the intestine and muscles, and intestinal microbial community alterations.